2021
DOI: 10.3389/fvets.2021.703101
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Flow Cytometric Semen Analysis and miRNA Profiling as a Tool to Discriminate Between High- and Low-Fertility Bulls

Abstract: Predicting bull fertility is one of the main challenges for the dairy breeding industry and artificial insemination (AI) centers. Semen evaluation performed in the AI center is not fully reliable to determine the level of bull fertility. Spermatozoa are rich in active miRNA. Specific sperm-borne miRNAs can be linked to fertility. The aim of our study is to propose a combined flow cytometric analysis and miRNA profiling of semen bulls with different fertility to identify markers that can be potentially used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Knockdown of FoxO1, FoxO2 and FoxO4 genes has been shown to impair mouse preimplantation embryonic development ( 66 ). In the current study, it is difficult to decipher the collective actions of the differentially expressed miRNAs, but from previous studies it is likely that these miRNAs have an effect on early embryo development, prior to embryonic genome activation ( 23 , 67 ). Further analyses, carried out on embryos generated with the semen from HF and LF bulls, is needed to corroborate this.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Knockdown of FoxO1, FoxO2 and FoxO4 genes has been shown to impair mouse preimplantation embryonic development ( 66 ). In the current study, it is difficult to decipher the collective actions of the differentially expressed miRNAs, but from previous studies it is likely that these miRNAs have an effect on early embryo development, prior to embryonic genome activation ( 23 , 67 ). Further analyses, carried out on embryos generated with the semen from HF and LF bulls, is needed to corroborate this.…”
Section: Discussionmentioning
confidence: 91%
“…Capra et al ( 22 ) identified 83 differentially expressed miRNAs between bulls with high and low motile spermatozoa, with these miRNAs targeting biological pathways related to apoptosis. Recently, Turri, et al ( 23 ) reported 13 differentially expressed miRNAs between HF and LF with miR-423-3p highly expressed among LF bulls, which is known to be associated with severe asthenozoospermia in human spermatozoa. In the same study, miR-191 had increased expression in HF bulls and has previously been positively associated with the fertilization rate of blastocysts ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sire conception rate showed a positive correlation with relative sperm volume shift [ 35 ] and acrosome reacted sperm at 5 h post-thaw [ 34 ], no correlation with hypoosmotic swelling [ 35 ], negative correlation with lipid peroxidation [ 171 ], sperm DNA fragmentation, and plasma membrane integrity [ 172 ]. Turrri et al (2021), observed a positive association of field fertility (estimated relative conception rate), semen quality parameters (sperm kinetics and DNA), and specific miRNAs (15 differentially expressed miRNAs (including nine known miR-2285n, miR-378, miR-423-3p, miR-191, miR-2904, miR-378c, miR-431, miR-486, miR-2478)) between high- and low-fertility bulls [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are highly stable in biofluids. Expression of miRNAs is detectable in sperm and seminal plasma of all animal species [ 17 , 18 , 19 , 20 , 21 , 22 ]. The miRNA expression is greater in sperm compared to seminal plasma and follows a similar expression trend [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spermatozoal miRNAs have been reported in healthy bulls and those differeing in their spermatozoal motility or fertility ( Table 3 ). The whole miRNA profiling of bull spermatozoa through deep sequencing identified 2022 miRNAs and included a large number of isomiRs across different species ( Turri et al, 2021 ). RNA-seq analysis of high fertility and low fertility bulls reported nine DE miRNAs (miR-2285n, miR-378, miR-423-3p, miR-19, miR-2904, miR-378c, miR-431, miR-486, and miR-2478) in which miR-2285n, miR-378, and miR-486 were observed to have altered expression levels between low and high motile sperm.…”
Section: Introductionmentioning
confidence: 99%